Peran Media dalam Mencegah Kriminalisasi Pembela HAM: Strategi Advokasi dan Konsep Perlindungan - Indah Dwi Putri; Voleta Sela Syahda (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The criminalization of human rights defenders in Indonesia remains a serious issue. Amnesty International Indonesia's report in the first half of 2025 recorded more than a hundred cases of attacks and criminalization against human rights defenders, including journalists, indigenous peoples, and environmental activists. This situation demonstrates the state's weak protection of human rights defenders and the increasing urgency of the media's role in public advocacy. This article aims to analyze how the media can play a role in preventing the criminalization of human rights defenders through advocacy strategies, while offering a concept of protection that can strengthen their position before the law. This study uses a normative juridical method with a conceptual and case approach, namely analyzing relevant national and international legal instruments and examining the practice of criminalizing human rights defenders through media coverage. The results of the study show that the media has a dual role, namely as a means of advocacy to pressure the state to be accountable and as a space for shaping public opinion that protects human rights defenders from negative stigma. The concept of protection offered is the optimization of the media as an advocacy actor based on the principles of transparency, accountability, and public participation.